Studi Tentang Profesionalisme Pimpinan Dalam Meningkatkan Kinerja Aparatur Pada Kantor Desa Gas Alam Badak I Kecamatan Muara Badak Kabupaten Kutai Kartanegara. - Saksono, Agus Noerman (PREDIKSI, 2014)
The purpose of this research is to find out whether the positive role against the leadership of the professional performance of the employees of the Bapemas And Pemdes of East Kutai Regency to get the data the author doing such research. The results showed that the leadership was instrumental to the performance of the employees of the apparatus, in the sense that the performance factors Bapemas And Pemdes employees apparatus Kutai Regency East from month to month and even from year to year changes are increasing. This was followed by the professionalism of the leadership in this case serves as a variable for it. To improve the performance of the apparatus, in addition to other factors then the leadership factor needs to get attention so work achievement officers of Bapemas And Pemdes of East Kutai Regency could be improved.